PENERAPAN ART THERAPY UNTUK MENGURANGI PERILAKU MENYAKITI DIRI SENDIRI (SELF-INJURIOUS BEHAVIOR) PADA DEWASA MUDA YANG MENGALAMI DISTRESS PSIKOLOGIS - Dinar Saputra (Universitas Paramadina, 2019)
The aim of this research is to identify the decline of Self-Injurious Behavior of young adults who experience psychological distress after participating in art therapy intervention. Self-injurious behaviour (SIB) is a problem that often occurs to some individuals who because they are unable to manage their stress and express it in positive ways. SIB is a direct and intentional behavior to create destructive conduct to themselves without having any intention to commit suicide, but usually it is used as a negative coping of individual’s emotional problem (Walsh, 2007). The pressure can be influence by the their psychological distress. To avoid and address any posibility of the negative impacts that will occur to SIB patient, an appropriate psychological intervention is necessary being implemented. In this research art therapy is being used as one of thesecured media for emotional catharsis. The design of the research is single subject experiment using the combination of qualitative and quantitative methods on three participants. Data collection was conducted by, interviews and observations. Subjective Unit Distress (SUDS) was utilized to obtain quantitative measurement. Result based on The Self-Injury Questionnaire-Treatment Related (SIQ-TR) and Self-Injury Behavior Scale (SIB) indicate that the SIB of the three participants were reduced after participating in art therapy.